Ruska agresija na Ukrajino - Štrucl, Damjan (Sodobni vojaški izzivi, 2022)
The contemporary security environment is global, dynamic, and unpredictable, particularly in terms of providing cyber security and cyber defence. Numerous analyzes of Russian hybrid operations have shown that the Russian Federation is conducting a number of cyber operations to achieve its politically strategic goals. Despite such debates, the Russo-Ukrainian war represents a new turning point in the global security environment, as many non-state actors have become involved in the conflict and cyberspace has become a tool for implementing sanctions. Thus, the article aims to analyze the implementation of cyber operations of the Russian Federation as observed in the case of its military aggression against Ukraine and the potential global impact of cyberspace in armed conflict for the future.
Keywords: kibernetika; kibernetski napadi; Kibernetski prostor; Kibernetski terorizem; obrambna politika; Rusija; Ukrajina; varnost